Conditional stability of quasitoroidal manifolds of systems of partial differential equations - Tkach, B. P. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We investigate the problem of conditional stability of quasitoroidal manifolds of a system of partial differential equations.